The SlDLK2 receptor, involved in the control of arbuscular mycorrhizal symbiosis, regulates hormonal balance in roots - Ramos-Alvelo, Martín; Molinero-Rosales, Nuria; Tamayo-Navarrete, María Isabel; Ćavar Zeljković, Sanja; Tarkowski, Petr; García-Garrido, José Manuel; Ho-Plágaro, Tania (Frontiers in Microbiology, 2024)
Arbuscular mycorrhiza (AM) represents a symbiotic mutualistic association between most land plants and Glomeromycota fungi. AM fungi develops specialized intraradical and highly branched structures, called arbuscules, where bidirectional exchange of nutrients between plant and fungi partners occurs, improving plant growth and fitness. Transcriptional reprogramming and hormonal regulation are necessary for the formation of the arbuscules. SlDLK2, a member of the third clade from the DWARF14 family of α, β-hydrolases closely related to the strigolactone receptor D14, is a negative regulator of arbuscule branching in tomato, but the underlying mechanisms are unknown. We explored the possible role of SlDLK2 on the regulation of hormonal balance. RNA-seq analysis was performed on roots from composite tomato plants overexpressing SlDLK2 and in control plants transformed with the empty vector. Analysis of transcriptomic data predicted that significantly repressed genes were enriched for genes related to hormone biosynthesis pathways, with a special relevance of carotenoid/apocarotenoid biosynthesis genes. Stable transgenic SlDLK2 overexpressing (OE) tomato lines were obtained, and hormone contents were analyzed in their roots and leaves. Interesting significant hormonal changes were found in roots of SlDLK2 OE lines with respect to the control lines, with a strong decrease on jasmonic acid and ABA. In addition, SlDLK2 OE roots showed a slight reduction in auxin contents and in one of the major strigolactones in tomato, solanacol. Overall, our results suggest that the negative regulation of AM symbiosis by SlDLK2 is associated with the repression of genes involved in the biosynthesis of AM-promoting hormones.